Factors Influencing Loss to Follow-Up in HIV Patients: a Retrospective Study - Theresia Natalia Seimahuira; Johan Weinand Lepertery; Azzahra, Fatimah; Ahmad Rabitha Alam Arfah; Chelvano Yason Matitaputty (Faculty of Medicine, Universitas Airlangga, 2025)
Background: HIV has become a global health problem, causing millions of deaths since its discovery. The success of antiretroviral therapy (ART) depends heavily on patient adherence, yet the lost-to-follow-up (LTFU) rate remains high. Purpose: This study aims to identify the characteristics of HIV patients experiencing LTFU and analyze the influencing factors at the Karang Panjang Community Health Center in Ambon City. Methods: This study employs a cross-sectional design with secondary data analysis from theedical records of HIV patients from 2018 to 2024. The sampling technique used was total sampling, with a total sample size of 152 patients. Data analysis was conducted descriptively and inferentially using the chi-square and Fisher’s exact test. Result: The prevalence of LTFU among HIV/AIDS patients at the Karang Panjang Community Health Center is 15.1%. Most LTFU patients are female, over 30 years old, and married. Statistical tests show significant associations between LTFU and age (p = 0.0468), sex (p = 0.0433), and marital status (p = 0.0355), while education and religion are not significant. Among LTFU cases, 8.3% had died, 50% were alive but had stopped therapy, and 41.7% were untraceable. Additional contributing factors identified through discussions and medical record reviews include inadequate counseling and education, poor documentation of ARV side effects, limited financial resources, and insufficient peer or family support. Conclusion: The study concludes that age, sex, and marital status contribute to LTFU among HIV patients. It recommends improving ART retention through education, stricter monitoring, and community-based strategies to reduce future LTFU rates.